Identification of TMEM206 proteins as pore of PAORAC/ASOR acid-sensitive chloride channels - Ullrich, Florian; Blin, Sandy; Lazarow, Katina; Daubitz, Tony; von Kries, Jens Peter; Jentsch, Thomas J (eLife, 2019)
Acid-sensing ion channels have important functions in physiology and pathology, but the molecular composition of acid-activated chloride channels had remained unclear. We now used a genome-wide siRNA screen to molecularly identify the widely expressed acid-sensitive outwardly-rectifying anion channel PAORAC/ASOR. ASOR is formed by TMEM206 proteins which display two transmembrane domains (TMs) and are expressed at the plasma membrane. Ion permeation-changing mutations along the length of TM2 and at the end of TM1 suggest that these segments line ASOR’s pore. While not belonging to a gene family, TMEM206 has orthologs in probably all vertebrates. Currents from evolutionarily distant orthologs share activation by protons, a feature essential for ASOR’s role in acid-induced cell death. TMEM206 defines a novel class of ion channels. Its identification will help to understand its physiological roles and the diverse ways by which anion-selective pores can be formed.